Programmed death-ligand 1 expression profiling in thymic epithelial cell tumors: clinicopathological features and quantitative digital image analyses - Ishihara, Shunta; Okada, Satoru; Ogi, Hiroshi; Kodama, Yoshinori; Shimomura, Masanori; Tsunezuka, Hiroaki; Itoh, Kyoko; Marx, Alexander; Inoue, Masayoshi (Lung cancer, 2020)
Objectives - Whether the extent of expression of programmed death-ligand 1 (PD-L1) is clinically significant remains uncertain, although immuno-oncological features have been studied in thymic epithelial cell tumors (TETs). We investigated the histological features of PD-L1 expression in TETs, and assessed PD-L1 expression using digital image analysis. - Materials and Methods - Participants comprised 66 patients with TET who underwent surgical resection between 2001 and 2016. We calculated tumor cell-positive ratio as total proportion score (TPS) with immunohistochemistry using SP263 anti-PD-L1 monoclonal antibody. PD-L1 expression was also quantified using digital image analysis of whole-slide images. We evaluated the relationship between conventional visual TPS using optical microscopy (TPS-V) and TPS from digital image analysis (TPS-IA). We further classified all TETs into high or low PD-L1 expression groups and assessed the clinical significance of PD-L1 expression level using TPS-V and TPS-IA. - Results - WHO histological types were Type A (n=8), AB (n=18), B1 (n=5), B2 (n=16), B3 (n=6), metaplastic thymoma (n=2), and thymic carcinoma (TC) (n=11). Median TPS-Vs were 2%, 2%, 10 %, 65 %, 90 %, 1%, and 20 %, respectively. TPS-IAs correlated with TPS-Vs in TETs overall and in thymomas, but not in TCs. PD-L1 expression levels in TETs differed significantly among histological types. Whether TPS-V or TPS-IA were used, the PD-L1high group included more cases of the more aggressive histological types. Recurrence-free survival (RFS) was shorter in the PD-L1high group than in the PD-L1low group in thymoma using TPS-IA, whereas RFS of the PD-L1high group was shorter in all TETs using TPS-V. - Conclusion - PD-L1 expression levels depended on the histological type of TET. Extensive PD-L1 expression in TETs was associated with poor prognosis. Digital image analysis is feasible for evaluating PD-L1 expression in TETs and might offer clinically relevant features of thymomas.